Inside-mode indium oxide/carbon nanotubes for efficient carbon dioxide electroreduction by suppressing hydrogen evolution. Issue 10 (8th January 2021) - He, Haichuan; Yang, Congcheng; Deng, Liu; Wu, Jian; Chen, Fei; Huang, Jianhan; Liu, You-Nian
Abstract : An inside-mode MWCNTs@In2 O3 compound was developed to improve the catalytic effect and suppress hydrogen evolution. The HCOOH selectivity reaches up to 92.2%. Abstract : The hydrogen evolution reaction is a huge challenge for CO2 electroreduction. Herein, an inside-mode indium oxide/carbon nanotube compound (MWCNTs@In2 O3 ) is developed to maximize the catalytic effect and suppress hydrogen evolution, its HCOOH selectivity can reach up to 92.2% at −16.8 mA cm −2, which is more efficient than In2 O3 .